May gawa na kaming natapus dini : si Rizal at ang wikang Tagalog - Ocampo, Nilo S.; University of the Philippines. Office of the Vice Chancellor for Research and Development (Diliman, Quezon City : Office of the Vice Chancellor for Research and Development, University of the Philippines, 2002)
Commentary on literary works of Jose Rizal written in Tagalog language.
Includes bibliographical references (p. 569-581) and index.
In Tagalog.
Keywords: Rizal, José, -- 1861-1896 -- Criticism and interpretation